REKAYASA NILAI RENATURALISASI SUNGAI BODRI LAMA TERHADAP SUNGAI PECUT, KABUPATEN KENDAL - Yanuar Danu Wijaya; Sriyana Sriyana; Frida Kistiani (Jurnal Karya Teknik Sipil, 2014)
Sedimentation in the estuary of the Bodri River have a major impact on the flooding problems in the area around the Bodri River. To overcome this by planning Normalization Pecut River which has a large enough funding, so it is necessary to value engineering. The purpose of this paper is to obtain solutions to problems of sedimentation, coastal erosion, seawater intrusion and flooding, know the function and cost of the initial design (Normalization Pecut River), as well as getting the design alternatives (Re-naturalization Bodri Lama River) as a substitute for the initial design, which is further than the value of the function and cost. In terms of the normalization function Pecut River hydrologic analysis of the calculation results obtained by the discharge of floods over 25 years, the amount of Q25=18.236 m3/sec. The amount of sediment transport Pecut River, is 47.267 tons/year. Results hydraulics analysis with HEC-RAS program occurs runoff groove along the river, which means there is a flood. To Re-naturalisation Bodri Lama River flood discharge when re-used 50 years the amount of Q50=61.58 m³/sec. With the Renaturalisation of Bodri Lama River can reduce flood discharge in Bodri River at 5.73%. Old Bodri river sediment transport, amounting to 159.408 tons/ year. The results of the HEC-RAS program checks the water level in the re-naturalization of the Bodri Lama River be lower, so the plan is safe from flooding. In terms of costs for normalization Pecut River RAB calculation results obtained by Rp.34.269.498.000,00 (in words: Three-Four Billion Two Hundred Sixty-Nine Million Four Hundred Ninety Eight Thousand), to Renaturalisasi Bodri Lama River at Rp.10.362.242.000,00 (in words: Ten Billion Three Hundred Sixty-Two Million Two Hundred Forty-Two Thousand). Based on the analysis of value engineering, Renaturalisasi Bodri Lama River generate cost savings of RP. 23,907,256,000.00 (in words: Twenty-Three Billion Nine Hundred and Seven Million Two Hundred Fifty Six Thousand Rupiah).